The Contribution of School Leadership to the Improvement of Science Management and Education Quality in Elementary Schools in Balaraja-Tangerang - Lili Nurlaili (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze and evaluate the contribution of school leadership to the improvement of science management and education quality in several elementary schools located in Balaraja, Tangerang. The research uses a qualitative approach with a case study method. Data collection is carried out through in-depth interviews, participatory observation, and the analysis of documents relevant to school management practices and the implementation of school leadership. The study’s respondents include the school head, teachers, administrative staff, and some parents to obtain a more comprehensive perspective on the effectiveness of the leadership applied in the schools. The research findings show that school heads who implement a transformational leadership style have been successful in creating a more conducive school climate for teaching and learning. This leadership style encourages active participation from teachers and staff in the decision-making process, which impacts an increased sense of responsibility and commitment to improving education quality. The school head also plays a significant role in ensuring that teachers receive regular training and professional development, ultimately improving their teaching competencies. Additionally, the study also finds that good school management, directly influenced by the school head’s leadership, has a significant impact on students’ academic achievements. School heads who are able to facilitate curriculum updates and innovations in teaching methods have contributed to this success. Technology-based development programs and improvements in educational facilities have also proven to increase student engagement in the learning process, which leads to improved academic performance.